PENGARUH PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) TERHADAP KEMAMPUAN BERFIKIR KRITIS SISWA PADA MATA PELAJARAN BIOLOGI DI MA NW KOTARAJA KELAS X TAHUN PELAJARAN 2014/2015 - Nunung Ariandani (UNIVERSITAS HAMZANWADI, 2017)
The purpose of this study was to determine the effect Effects of Problem Based Learning (Problem Based Learning) Critical Thinking Ability Of Students In Biology Lesson In Class X MA NW Kotaraja academic year 2014/2015. This type of research is experimental research. Data collection techniques to study the results of the essay test method. The research hypothesis testing using t-test is parametric with a significant level of 5%. Based on calculations for analysis prerequisite test that normality test can be concluded that the two samples come from populations with normal distribution because χ2hitung ≤ χ 2tabel, namely for the experimental class ≤ 6.563 and 11:07 a.m. to 11:07 a.m. ≤ 7,271 control class. As for the homogeneity test can be concluded that the samples come from a homogeneous population because Fhitung Ftable is 1:04 1.86. From the analysis of the test showed that the hypothesis H0 is rejected and Ha accepted as the price of -thitung ≤ - T1 values / 2α or thitung ≥ t1 / 2α, namely 4.365 ≥ 2.002. . It can be concluded that the influence of Influence There is Problem Based Learning (Problem Based Learning) Critical Thinking Ability Of Students In Biology Lesson In Class X Kotaraja NW MA Academic Year 2014/2015.